2022
DOI: 10.1093/jacamr/dlac118
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of antibiotic stewardship programmes in paediatric patients in regional referral hospitals in Tanzania: experience from prescribers and dispensers

Abstract: Background In 2017, Tanzania launched the National Action Plan for Antimicrobial Resistance (NAPAR), 2017–2022 and implementation of antibiotic stewardship programmes (ASPs) was one of the agendas. Since the launch of the National Action Plan, no study has been done to assess its implementation. Objectives To explore the experiences of prescribers and dispensers on implementing ASPs among paediatric patients attending Regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…15 This may reflect the impact of AMS under the NAP implementation. 16,34,35 Limitations of the study…”
Section: Discussionmentioning
confidence: 99%
“…15 This may reflect the impact of AMS under the NAP implementation. 16,34,35 Limitations of the study…”
Section: Discussionmentioning
confidence: 99%
“…The lower rates for the other strategies under the various core elements can be attributed to challenges faced in their implementation [ 28 ]; thus, there is a need for additional training of pharmacists to expand their roles and capabilities in outpatient antimicrobial stewardship activities. Nkinda L. et al, (2022) reported a dearth of laboratory facilities to support culture and susceptibility tests, the absence of materials and reagents, pressure from management to avoid loss or to generate income, interference from patients, and inadequate training opportunities as barriers to the implementation of the stewardship activities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recently launched AWaRe book giving treatment guidance on a range of infectious diseases found in ambulatory care should help in this regard going forward [22,23]. Future activities could also include upgrading the curricula for HCPs to better equip them with the necessary confidence and skills to improve prescribing across the sectors [75,142,143]. Universities should also upgrade their continuous professional development (CPD) activities to address concerns with the knowledge and practices of HCPs in ambulatory care settings across Tanzania.…”
Section: Knowledge and Attitudes Concerning Antibiotics And Amr Among...mentioning
confidence: 99%